Tempe Lake Flood Challenges Inspire Community Adaptation, Wajo District, Indonesia - Riri Amandaria; Idham Irwansyah Idrus; Sopian Tamrin (JED (Jurnal Etika Demokrasi), 2024)
The Tempe Lake area is faced with flooding problems that routinely cause losses and disrupt the survival of households. This research was conducted in Tempe sub-district, located in Wajo district, South Sulawesi, presenting an important segment of the wider Tempe Lake region with using a case study approach, the research focused on households in the Lake Tempe community. This study examines the resilience of households inundated by flooding, focusing on income stability, settlement sustainability, food security, disease prevention, and disaster management patterns. The results revealed that the people of Tempe Lake have an extraordinary ability to harmonise tradition and innovation, allowing them to survive and thrive. The cleverness of the community is evident in the raising of the floor of houses to adjust to the ever-changing water levels, making footbridges for access to fellow residents and to public spaces, using sampan boats as a means of water transport, facilitating mobility to farms and public spaces, and alternative businesses, with the support of the local government and other institutions that sustain the lives of flood-affected communities. Remarkably, despite the constant flooding, people still choose to stay because they are driven by the close bonds of their community and the many income opportunities derived from rice farming, capture fisheries, and various job prospects in the vibrant city centre of Sengkang which makes the existence of Tempe Lake beautiful. Thus, the pattern of community adaptation is a knowledge that can be used as a reference for disaster management agencies in formulating a comprehensive work plan